Enhancement of nitrogen use efficiency through agronomic and molecular based approaches in cotton - Chattha, Muhammad Sohaib; Ali, Qurban; Haroon, Muhammad; Afzal, Muhammad Junaid; Javed, Talha; Hussain, Sadam; Mahmood, Tahir; Solanki, Manoj K.; Umar, Aisha; Abbas, Waseem; Nasar, Shanza; Schwartz-Lazaro, Lauren M.; et al. (Frontiers in Plant Science, 2022)
Cotton is a major fiber crop grown worldwide. Nitrogen (N) is an essential nutrient for cotton production and supports efficient crop production. It is one of the crucial nutrients which is required more than any other nutrients. Nitrogen management is a daunting task for plants; thus, various strategies individually and collectively are adopted to improve its use efficacy. Negative environmental impacts of excessive N application in cotton production have become eminent with harmful for consumers and growers. 4R’s (right product, right rate, right time, and right place) nutrient stewardship is considered a newly developed agronomic practice that provides a solid foundation in achieving nitrogen use efficiency (NUE) in cotton production, which is also equally crucial for cropping systems for increasing production, increasing grower’s profitability, environmental growth protection, and enhancing sustainability. This concept incorporates the right fertilizer source at the right rate at the right time and in the right place. Apart from agronomic practices, molecular approaches are also equally important for improving cotton NUE. This could be possible by increasing the efficacy of metabolic pathways at the cellular, organ, and structural levels and NUE regulating enzymes and genes. This is a potential way to improve the N transporter's role in the plant, resulting in better utilization and remobilization of N in the cotton plant. Therefore, we have suggested these effective methods to accelerate NUE in cotton. This review aims to add a detailed overview of the agronomic and molecular approaches for improving NUE in cotton production, which is beneficial for both the environment and growers.